2007
DOI: 10.1111/j.1469-8749.2006.tb01363.x
|View full text |Cite
|
Sign up to set email alerts
|

Coping with Dravet syndrome: parental experiences with a catastrophic epilepsy

Abstract: The aim of this study was to investigate how parents cope with and care for a child with Dravet syndrome, a severe myoclonic epilepsy with three distinct stages. Twenty‐four parents of children with Dravet syndrome participated in a semi‐structured interview and 17 completed the Impact of Childhood Neurologic Disability Scale (ICND) questionnaire. Children included 11 males and 13 females aged 2 to 24 years (mean age 10y 2mo [SD 5y 8mo]). Stage 1 of the syndrome was generally very difficult. Uncertainty about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 14 publications
0
24
0
Order By: Relevance
“…A relationship between altered SCN1A function and sleep disturbances has also been noted. For instance, parents have observed that children with Dravet syndrome experience difficulty falling asleep and staying asleep (Nolan et al, 2006), and electroencephalography (EEG) recordings of adolescents with Dravet syndrome reveal frontal slow spikes during wakefulness and sleep (Nabbout et al, 2008). In addition, two brothers with the SCN1A mutation S1713N exhibited diffused slow spike and wave complexes during sleep and abnormal paralysis of the muscle mentalis during non-rapid eye movement (NREM) sleep (Kimura et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…A relationship between altered SCN1A function and sleep disturbances has also been noted. For instance, parents have observed that children with Dravet syndrome experience difficulty falling asleep and staying asleep (Nolan et al, 2006), and electroencephalography (EEG) recordings of adolescents with Dravet syndrome reveal frontal slow spikes during wakefulness and sleep (Nabbout et al, 2008). In addition, two brothers with the SCN1A mutation S1713N exhibited diffused slow spike and wave complexes during sleep and abnormal paralysis of the muscle mentalis during non-rapid eye movement (NREM) sleep (Kimura et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Reactions and priorities varied according to where a family was in the disease journey which, for early-life epilepsies, closely corresponds to the age of the child. 9 As one parent expressed, there are four stages: initial shock of diagnosis, treatment odyssey where families try one therapy after another, desperation because "we're running out of options," and then desolation and questioning "how long can we keep doing this?" In addition, the realization settles in, as a child grows older, that the hoped-for improvements may never occur.…”
Section: Stage In the Disease Journeymentioning
confidence: 99%
“…Nolan distinguished four phases in Dravet syndrome representing the different impacts of seizures versus behavioral morbidities over time but begin with the shock of diagnosis and uncertainty. 9 Our participants highlighted the disease path as having a thread that went from hope that things would get better to dashed hopes of finding a solution and realization that the situation was never going to improve.…”
Section: Modulating Factorsmentioning
confidence: 99%
“…Nine studies reported 3 different key process level variables, including parental and child psychosocial and health care needs 22,24,42,43 and coping. 23,38,39,46,55 Data from these studies suggested that parents and children have support and information needs, as measured by the Parent and Child Report of Psychosocial Care, 56,57 related to their epilepsy that should serve to enhance self-management behaviors if this level of information was provided. Difficulty in coping with epilepsy was conceptualized as a barrier to effective self-management, which could also be considered a target for interventions to improve selfmanagement.…”
Section: Processesmentioning
confidence: 99%